A Centralized Win-Win Cooperative Framework for Wi-Fi and 5G Radio Access Networks. (8th September 2021) - Raschellà, A.; Aldhaibani, O.; Pizzi, S.; Mackay, M.; Bouhafs, F.; Araniti, G.; Shi, Q.; Lucas-Estañ, M. C.
Abstract : Cooperation to access wireless networks is a key approach towards optimizing the use of finite radio spectrum resources in overcrowded unlicensed bands and to help satisfy the expectations of wireless users in terms of high data rates and low latency. Although solutions that advocate this approach have been widely proposed in the literature, they still do not consider a number of aspects that can improve the performance of the users' connections, such as the inclusion of (1) cooperation among network operators and (2) users' quality requirements based on their applications. To fill this gap, in this paper we propose a centralized framework that is aimed at providing a "win-win" cooperation among Wi-Fi and cellular networks, which takes into account 5G technologies and users' requirements in terms of Quality of Service (QoS). Moreover, the framework is supported by smart Radio Access Technology (RAT) selection mechanisms that orchestrate the connection of the clients to the networks. In particular, we discuss details on the design of the proposed framework, the motivation behind its implementation, the main novelties, its feasibility, and the main components. In order to demonstrate the benefits of our solution, we illustrate efficiency results achieved through the simulation of a smart RAT selection algorithm in a realistic scenario, which mimics the proposed "win-win" cooperation between Wi-Fi and cellular 5G networks, and we also discuss potential benefits for wireless and mobile network operators.